The correct answer is C. m-1(x) = [tex] \frac{x + 5}{5} [/tex]
You can find the value of any inverse function by switching the m(x) and the x value. Then you can solve for the new m(x) value. The end result will be your new inverse function. The step-by-step process is below.
m(x) = 5x - 5 ----> Switch m(x) and x
x = 5m(x) - 5 ----> Add 5 to both sides
x + 5 = 5m(x) ----> Divide both sides by 5
[tex] \frac{x + 5}{5} [/tex] = m(x) ----> Change the order for formatting purposes.
m(x) = [tex] \frac{x + 5}{5} [/tex]
And this would be your inverse, which matches answer C.